2008
DOI: 10.1111/j.1439-0531.2008.01170.x
|View full text |Cite
|
Sign up to set email alerts
|

Mastitis in Post‐Partum Dairy Cows

Abstract: Transition from the dry period to lactation is a high risk period for the modern dairy cow. The biggest challenge at that time is mastitis. Environmental bacteria are the most problematic pathogens around parturition. Coliforms are able to cause severe infections in multiparous cows, and heifers are likely to be infected with coagulase-negative staphylococci. During the periparturient period, hormonal and other factors make the dairy cows more or less immunocompromised. A successful mastitis control programme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 68 publications
(94 reference statements)
0
35
0
1
Order By: Relevance
“…The reduction in the ability to mount an effective immune response is influenced by the extent of NEB around calving (Pyörälä 2008;Wathes et al 2009) because it is an energetically demanding process (Fox et al 2005). Acute infections cause local insulin resistance (Drobny et al 1984) and we have shown previously that a-2-HS-glycoprotein (AHSG) and pyruvate dehydrogenase kinase, isozyme 4 (PDK4), two genes implicated in insulin resistance, are upregulated in the endometrium when cows are in severe NEB, with the expression of both genes showing a significant positive correlation with circulating NEFA concentrations .…”
Section: Uterusmentioning
confidence: 99%
“…The reduction in the ability to mount an effective immune response is influenced by the extent of NEB around calving (Pyörälä 2008;Wathes et al 2009) because it is an energetically demanding process (Fox et al 2005). Acute infections cause local insulin resistance (Drobny et al 1984) and we have shown previously that a-2-HS-glycoprotein (AHSG) and pyruvate dehydrogenase kinase, isozyme 4 (PDK4), two genes implicated in insulin resistance, are upregulated in the endometrium when cows are in severe NEB, with the expression of both genes showing a significant positive correlation with circulating NEFA concentrations .…”
Section: Uterusmentioning
confidence: 99%
“…In dairy cows, incidence of intramammary infections increases during and around the dry period of a lactation cycle (Oliver and Sordillo 1988;Pyörälä 2008), and such infection may be a cause of mastitis in the early lactation stage. The incidence of clinical mastitis actually increases after calving (Bradley and Green 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of clinical mastitis actually increases after calving (Bradley and Green 2004). To prevent mastitis early after parturition, diagnosis, management, and therapeutics during the dry period are important (Pyörälä 2008), resulting in preventing or decreasing milk production losses in the early stage of lactation. Foremilk and milk contain proteins derived from plasma and tissue in addition to milk-specific proteins (Wall et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Animals at the first calving showed the lowest value of SCC compared to animals at the second calving order. Animals at the first calving have less contact with infectious agents, which confirms the lowest result of SCC (Pyörälä, 2008). Moreover, animals that had multiple lactations and consequently older age have higher chances of infection.…”
Section: Resultsmentioning
confidence: 67%